Fitness trends in Puerto Vallarta and Bahia of Banderas, Mexico: A prospective study toward 2026 - Paola Cortes Almanzar; Araceli Anayanzi Valencia Sandoval; Jorge López-Haro; Adrian Ricardo Pelayo Zavalza; Lino Francisco Jacobo Gómez Chávez (Journal of Sports and Physical Activity, 2026)
Background: Research on fitness sector trends represents a strategic resource for understanding changes in physical conditioning practices and emerging social demands related to health and well-being. This study extends the American College of Sports Medicine’s (ACSM) Worldwide Survey of Fitness Trends by integrating a regional longitudinal framework within a tourism-based metropolitan economy, an approach that remains underexplored in Latin American contexts. Aims: To identify and compare the main fitness trends projected for 2026 in the Puerto Vallarta–Bahía de Banderas region, examining their evolution over time and their alignment with national fitness trends in Mexico. Methods: A descriptive, comparative, and longitudinal design was employed using an adapted version of the ACSM Worldwide Survey of Fitness Trends. Data were collected through a digital questionnaire administered to fitness and health professionals via a non-probabilistic snowball sampling strategy between April and May 2025. The final sample consisted of 218 professionals working in the study region. Results: Exercise for body weight control, traditional strength training, and commercial or multi-purpose gyms emerged as the leading trends for 2026. Additionally, priorities related to mental health, youth sports development, and service digitalization gained prominence. Approximately 60% of the locally projected fitness trends coincide with national trends in Mexico, although differences in hierarchical positioning reflect the region's contextual specificities. Conclusion: These findings demonstrate a diversification of the regional fitness sector that combines consolidated practices with emerging social and technological demands. Academically, the study contributes a localized longitudinal perspective to the global fitness trends literature, while practically informing professional training, business strategies, and public health–oriented decision-making in tourism-driven urban regions.